PENGARUH PROTEAN CAREER TERHADAP CAREER OPTIMISM DENGAN CAREER DECISION SELF EFFICACY DAN CAREER ADAPTABILITY SEBAGAI PEMEDIASI PADA GENERASI MILENIAL DI SURAKARTA - Fitri Amalia; Jati Waskito (POLITEKNIK LP3I JAKARTA, 2024)
This study aims to analyze the effect of the influence of Protean Career on Career Optimism with Career Decision Self Efficacy and Career Adaptability as mediators in the millennial generation in Surakarta. In this study, the population used is the Surakarta millennial generation, aged between 27 and 42 years. Due to the unknown population, the calculation required to determine the minimum sample size is Malhottra's calculation. The sampling technique uses purposive sampling method which is included in the non probability sampling technique. The data used in this research is primary data. Primary data was used in the preparation of this study, this data was obtained through respondents' answers from a closed questionnaire. The data collection method used in this research is a questionnaire. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The results showed that protean career has a positive and significant effect on career decision self-efficacy. Protean career has a positive and significant effect on career optimism. Protean career has a positive and significant effect on career adaptability. Career decision self-efficacy has a positive and significant effect on career optimism. Career adaptability has a positive and significant effect on career optimism. Protean career has a positive and significant effect on career optimism through career decision self-efficacy. Protean career has a positive and significant effect on career optimism through career adaptability. Keywords: Protean Career, Career Optimism, Career Decision Self Efficacy, Career Adaptability